Segmenting into Adequate Units for Automatic Recognition of Emotion-Related Episodes: A Speech-Based Approach - Anton Batliner; Dino Seppi; Stefan Steidl; Björn Schuller (Advances in Human-Computer Interaction)
We deal with the topic of segmenting emotion-related (emotional/affective) episodes into adequate units for analysis and automatic processing/classification—a topic that has not been addressed adequately so far. We concentrate on speech and illustrate promising approaches by using a database with children's emotional speech. We argue in favour of the word as basic unit and map sequences of words on both syntactic and ‘‘emotionally consistent” chunks and report classification performances for an exhaustive modelling of our data by mapping word-based paralinguistic emotion labels onto three classes representing valence (positive, neutral, negative), and onto a fourth rest (garbage) class.